A Proposed Diagnostic Algorithm for Inborn Errors of Metabolism Presenting With Movements Disorders - Ortigoza-Escobar, Juan Darío (Frontiers in Neurology, 2020)
Inherited metabolic diseases or inborn errors of metabolism frequently manifest with both hyperkinetic (dystonia, chorea, myoclonus, ataxia, tremor, etc.) and hypokinetic (rigid-akinetic syndrome) movement disorders. The diagnosis of these diseases is in many cases difficult, because the same movement disorder can be caused by several diseases. Through a literature review, two hundred and thirty one inborn errors of metabolism presenting with movement disorders have been identified. Fifty-one percent of these diseases exhibits two or more movement disorders, of which ataxia and dystonia are the most frequent. Taking into account the wide range of these disorders, a methodical evaluation system needs to be stablished. This work proposes a six-step diagnostic algorithm for the identification of inborn errors of metabolism presenting with movement disorders comprising red flags, characterization of the movement disorders phenotype (type of movement disorder, age and nature of onset, distribution and temporal pattern) and other neurological and non-neurological signs, minimal biochemical investigation to diagnose treatable diseases, radiological patterns, genetic testing and ultimately, symptomatic, and disease-specific treatment. As a strong action, it is emphasized not to miss any treatable inborn error of metabolism through the algorithm.